2014
DOI: 10.1177/0003489414565001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality of Life Improvement in Allergic Rhinitis Patients After Sublingual Immunotherapy

Abstract: Several factors were found that may predict QoL outcomes in AR patients following SLIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Whether the improvements that were found in this study reflect a global improvement in disease symptoms or are they a result of specific aspects is uncertain. While several factors may predict QoL outcomes in patients with AR following therapy, it has been reported that improvements in olfactory function and reduction in asthma symptoms may be of particular importance,24,25 both of which were seen in our cohort across the study period (Table 2). These were matched by the reduction in medication use by patients both with and without asthma (Figure 3).…”
Section: Discussionmentioning
confidence: 77%
“…Whether the improvements that were found in this study reflect a global improvement in disease symptoms or are they a result of specific aspects is uncertain. While several factors may predict QoL outcomes in patients with AR following therapy, it has been reported that improvements in olfactory function and reduction in asthma symptoms may be of particular importance,24,25 both of which were seen in our cohort across the study period (Table 2). These were matched by the reduction in medication use by patients both with and without asthma (Figure 3).…”
Section: Discussionmentioning
confidence: 77%
“…Our analysis does not permit comparison of the HRQL of AR patients with that of the general population; however, a Spanish cross-sectional study that investigated the overall HRQL of patients with AR using SF-12 reported that HRQL was 25 % lower than in the general population [ 79 ]. Poor HRQL in patients with AR is also supported by evidence that successful treatment of AR symptoms with AIT [ 21 23 ] or symptomatic treatment [ 24 – 31 ] improves patient’s HRQL scores. A comparison of published EQ-5D utility baseline scores indicated that perennial allergy and/or AA (13 patients with AR and 12 with AR+AA), on a typical day with allergy symptoms, had a score of 0.60 [ 23 ], indicating comparable HRQL to diabetes (0.83) [ 80 ], cardiovascular disorders (0.73), musculoskeletal disorders (0.63), and psychosomatic disorders (0.57), when measured with the same EQ-5D instrument [ 81 ].…”
Section: Discussionmentioning
confidence: 96%
“…There is now considerable evidence that the symptoms of AR and AA negatively affect patients’ health-related quality of life (HRQL) [ 11 20 ]. This is supported by evidence that successful treatment of symptoms with allergy immunotherapy (AIT) [ 21 23 ] or symptomatic treatments [ 24 – 31 ] improves the HRQL of patients with AR. These improvements generally mirror those of conventional clinical outcome measures, such as symptom and medication scores, and lung function tests [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Underestimation of symptoms is also supported by our findings, according to which, half of the patients evaluated their symptoms severity as mild, with 32% reporting some concern and only 16.5% reporting moderate-to-severe disease. Self-reported symptom-free cases make early screening and diagnosis, as well as early treatment, clinically meaningful to prevent future disease comorbidities (e.g., asthma and chronic rhinosinusitis) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although AR has recently been divided according to the ARIA classification into intermittent versus persistent based on the duration of symptoms [ 34 ], allergen-specific treatment also needs to be incorporated with the seasonal and perennial classification to ascertain the correct allergen to be used in desensitization [ 37 ]. Therefore, according to seasonality, subjects with PAR described their symptoms as moderate-to-severe, but patients with SAR had milder symptoms.…”
Section: Discussionmentioning
confidence: 99%